Water demand and growth of cowpea (Vigna unguiculata (L.) Walp.) under doses of sheep manure - Borborema, Lucyelly Dâmela Araújo; Ferraz, Rener Luciano de Souza; Costa, Patrícia da Silva; Gonzaga, Giordano Bruno Medeiros; Medeiros, Aldair de Souza (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
The Brazilian semi-arid region has water restrictions, which justifies the cultivation of cowpea associated with sustainable soil management practices. Thus, the objective of this work was to evaluate the water demand and growth of cowpea under doses of sheep manure in the Cariri region of Paraíba. The experiment was carried out in the municipality of Soledade, Paraíba, using a completely randomized design, testing six doses of sheep manure (D1 = 0%, D2 = 5%, D3 = 10%, D4 = 15%, D5 = 20% and D6 = 25%, m/m) and 4 repetitions, totaling 24 experimental units. Water demand was determined during cultivation and at 10 and 22 days after sowing, the length of the main branch was measured, the leaf area estimated and the root, shoot and total dry mass determined. It was verified that doses of sheep manure increase the water demand and the growth of cowpea in the Cariri region of Paraíba, being recommended the application of a dose of 13.51±1.98% of sheep manure.